Mixed Generation Sensitivity Analysis: An Optimal Scenario Study. Issue 1 (14th October 2014) - Wilson, Reginald
Abstract There are several generating units available to meet the load demand on any given day. The mixed‐integer programme case engages generating units that can be shut down or operated between minimum and maximum output levels within a specific time demand block. An examination of these conditions espouses the utilization of renewable energy technology as a reliable power generation source and its effectiveness and augmentation in a robust, heavily subjugated thermal generation system. The mixed‐integer problem has the predisposition to generate many subproblems during the computation. However, with careful selection of the parameters in the model, the challenges are easily overcome. Hydroelectric energy is significant from an operational standpoint as it requires little or no ramp‐up time, commonly found in many combustion technologies. The essential load‐following capability, peaking capacity and voltage stability attributes render hydroelectric energy as a significant part in ensuring reliable electricity service and in meeting customer needs in a market‐driven industry. When this renewable resource is combined with the thermal generation, an improved reliability function is apparent. Yet, in order to minimize the environmental effects inherent in this type of energy resource, the renewable power supply is expected to produce an effectual, consistent output. The integration of renewable generation within the electrical system entails intricate analysis of the transmission line upgrades throughout the system. These upgrades are designed to relieve congestion, improve reliability and provide voltage support by thoroughly evaluating the alternatives to accommodate the new expansion efforts. This paper examines the system integration of renewable generators, via simulated studies, in the context of electrical operations from the hydroelectric generation perspective. Copyright © 2014 John Wiley & Sons, Ltd.